94 A qualitative study to explore the experiences and roles of early adopters in the early implementation of magnolia house, a new facility for sharing life-altering information and bereavement care. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Hilton, Anna; Shaw (PI), Karen; Cummins, Carole; Farre, Albert; Fitzmaurice, Nicki; Heath, Gemma
Abstract : Background: Magnolia House (MH) is a new, innovative facility at an acute paediatric hospital. It was built to improve the quality of care for families and staff involved with sharing life-altering information and bereavement, through transforming the environment in which care is delivered. However, implementing healthcare innovations is known to be challenging. This study therefore aimed to understand the experiences of the early adopters of MH to understand factors that promote, inhibit or define new models of palliative care in acute settings. Methods: Semi-structured interviews were undertaken with hospital staff who used MH in its first 3-months of opening (i.e. early adopters). Data collection and analysis were guided by implementation theories, including the Normalisation Process Theory (NPT). Interviews were recorded and transcribed and then analysed using a two-step process involving inductive thematic analysis followed by an examination of the findings in relation to the NPT. Results: The 30 participants were from a wide range of specialties. They had used MH for wide-ranging activities (treatment/prognosis discussions, advance care planning, treatment withdrawal, memory-making, bereavement care) and felt it improved care by providing privacy, removing distractions and facilitating the humanisation of care. However, issues were highlighted that influenced how MH was understood and used by staff, and have subsequently shaped the routine use of MH. These included issues relating to the practical management of MH, sense of ownership and shared understanding of purpose. Conclusion: The findings reveal important information about how palliative care can be improved in acute settings. They show how initial implementation strategies can influence staff engagement with innovations like MH and suggest factors that affect uptake and the quality of care. This work is informing the development of MH and has wider implications for how other acute settings can transform their care environments for the benefit of patients and families.